Akibat Hukum Perkawinan Janda Yang Dilangsungkan Sebelum Habis Jangka Waktu Tunggu - Lestari, Nur Reski (Universitas Muhammadiyah Jember, 2019)
The purpose of marriage as mentioned in Article 1 of Law Number 1 Year 1974 on Marriage is to establish a happy and eternal family (household) based on Belief in the One Supreme. Sometimes marriage does not go on forever, so there is a divorce. For a wife who breaks up her marriage applies to her waiting period or waiting period, unless a wife divorces her husband before she gets in touch. There are times when a marriage is canceled because it has been known that the waiting period has not been exhausted in a woman. However, on the other hand there is also a problem that marriage has taken place but it turns out the waiting period has not been exhausted. If in the conduct of marriage does not meet the legal requirements of his marriage, then the marriage tersebuh can be canceled. While cancellation can only be done through court decision. When a court decision aborts a marriage, the marriage is considered to have never occurred.